Chromium and selenium-enriched yeast for castrated finishing pigs: effects on performance and carcass characteristics - João Garcia Caramori Júnior; Charles Kiefer; Eduardo Viana Ferreira; Bruno Serpa Vieira; Henrique Carvalho Oliveira; Camila Mendonça Silva; Rodrigo Caetano Abreu; Uanderson Veríssimo de Luna (Semina: Ciências Agrárias, 2017)
To evaluate the effect of organic chromium (Cr) and selenium (Se) supplementation on performance and carcass characteristics of finishing pigs, 300 castrated males were distributed in a randomized block design with three treatments and five replications of 20 pigs each. Treatments consisted of different diets, formulated to reach or exceed Rostagno et al. (2011) nutritional requirements, as follows: 1) control - basal diet without organic Cr and Se supplementation from 70 to 130 kg of body weight; 2) CrSe70 - basal diet supplemented with 0.8 mg kg-1 of Cr- and 0.6 mg kg-1 of Se-enriched yeast from 70 to 130 kg of body weight; 3) CrSe100 - basal diet without organic Cr and Se supplementation from 70 to 100 kg of body weight followed by basal diet supplemented with 0.8 mg kg-1 of Cr- and 0.6 mg kg-1 of Se-enriched yeast from 100 to 130 kg of body weight. Performance was evaluated by measuring body weight, daily weight gain, daily feed intake and feed conversion ratio. At the end of experimental period, pigs were sacrificed and lean meat percentage, longissimus dorsi muscle depth, back fat thickness, and carcass bonus index were determined using prediction equations generated by the software Hennessy System GP4 after carcass scanning with an electronic probe. Data were submitted to one-way ANOVA and in case of significant differences (P ? 0.05), means were compared by SNK multiple-range test. Daily feed intake (P = 0.008) and feed conversion ratio (P = 0.004) decreased for pigs supplemented with Cr- and Se-enriched yeast from 70 to 100 kg of body weight. Otherwise, pigs supplemented between 100 and 130 kg of body weight increased (P = 0.032) daily feed intake in comparison to the control group. Regarding carcass characteristics, Cr- and Se-enriched yeast supplementation increased (P = 0.019) longissimus dorsi muscle depth in both CrSe70 and CrSe100 treatments. In conclusion, dietary supplementation of Cr- and Se-enriched yeast for castrated male pigs between 70 and 130 kg of body weight increases longissimus dorsi muscle depth in carcass without affecting final body weight or daily weight gain of the animals.